Perhutanan Sosial dalam Pengelolaan Sumber Daya Hutan Di Indonesia - Fadel Ikrar Jamika; Ali Amran; Iswandi Umar; Mulya Gusman (Pro-Life, 2023)
Forests are one of the living environments that are directly related to humans. The biggest problem in the forestry sector is the rate of deforestation and degradation. Management of forest resources with the community is a system of resource management that is carried out. Social forestry is a system of managing forest resources in state forest areas or private forests, which provides opportunities for local communities as main actors and partners to improve their welfare and realize forest sustainability. The results of the research reveal that forest management with the community is an example of social forestry implementation. The aim of forest management with the community is to encourage the management of forest resources through a combination of economic, ecological and social aspects in a proportional and professional manner. Keywords: Forest management, environment, social forestry